Project SUN: Pilot Study of a Culturally Adapted Smoking Cessation Curriculum for American Indian Youth. (March 2022) - Ramos, Guadalupe G.; Sussman, Steve; Moerner, Lou; Unger, Jennifer B.; Soto, Claradina
American Indian Alaska Native (AIAN) youth have disproportionately higher rates of commercial tobacco product use compared to other racial and ethnic groups in the U.S. These rates underscore a need for commercial tobacco product cessation interventions that are culturally informed. This project studied the development, implementation, and some impact data of an adapted version of Project EX, an evidence-based intervention for teen smoking cessation. Implementation challenges resulted in a change from a three-arm to a single-arm trial with 37 AIAN youth who participated in an eight-week curriculum. Intent-to-treat analysis with biochemical validation results indicated that 32% (N = 12/37) of youth quit smoking at the three-month follow-up. Participants reported being satisfied with the program overall and enjoying the culturally adapted activities. This study detailed the program's adaptation and lessons learned during implementation.